Rancang Bangun Sepeda Listrik Menggunakan Motor DC Brushless - Tianur; M. Bayu Anggoro Nurcahyo; Made Rahmawaty; Jajang Jaenudin (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
Along with the times, technology in the transportation sector continues to develop rapidly. This is marked by the emergence of vehicles that are modern and practical to use. One example is an electric bicycle. electric bikes are a new option in development and alternative transportation. Because of these problems, a tool was made that can turn an ordinary bicycle into an electric bicycle. So that bicycle owners simply and easily turn ordinary bicycles into electric bikes. This tool uses a battery as its energy source and has a speed regulator that is placed on the bicycle handlebar. Which functions as a PWM regulator via a pulse generator. When a bicycle user turns the gas trhotle on the bicycle handlebar, the brushless motor at the bottom near the bicycle pedal attached to the rear tire will receive a PWM signal. When the gas throttle is pulled, the electronic speed control will activate, so the brushless motor rotates. And a brushless motor drives the rear wheels of the bike. This simple electric bicycle has a maximum speed of 27.1 km / h with a maximum rider weight of 100 kg.